Urgensi Bahasa Arab Bagi Da’i - Intan, Hilda Marni (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
This paper attempts to reflect the urgency of Arabic language support for the preachers in delivering mission kindness